2021
DOI: 10.3390/antiox10050809
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Cytotoxicity and Its Effects in Redox Homeostasis and Energetic Metabolism in Papillary Thyroid Carcinoma Cell Lines

Abstract: High-dose of vitamin C (L-ascorbic acid, ascorbate) exhibits anti-tumoral effects, primarily mediated by pro-oxidant mechanisms. This cytotoxic effect is thought to affect the reciprocal crosstalk between redox balance and cell metabolism in different cancer types. Vitamin C also inhibits the growth of papillary thyroid carcinoma (PTC) cells, although the metabolic and redox effects remain to be fully understood. To shed light on these aspects, PTC-derived cell lines harboring the most common genetic alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 47 publications
(60 reference statements)
1
23
0
Order By: Relevance
“…The most investigated have been leukaemia [ 20 24 ], colon cancer [ 25 32 ], melanoma [ 33 37 ], pancreatic cancer [ 14 , 31 , 38 ] and prostate cancer [ 39 – 41 ]. Similar results have been described for the treatment of non-small-cell lung cancer (NSCLC) [ 16 ], breast cancer [ 31 , 42 ], ovarian cancer [ 31 , 43 , 44 ], hepatocellular carcinoma [ 45 , 46 ], malignant mesothelioma [ 47 , 48 ], thyroid cancer [ 49 , 50 ], oral squamous cell carcinoma [ 51 ], neuroblastoma [ 52 ] and glioma, including the difficult-to-treat glioblastoma multiform (GBM) [ 16 , 53 , 54 ].…”
Section: High-dose Vitc As a Single Agentsupporting
confidence: 69%
“…The most investigated have been leukaemia [ 20 24 ], colon cancer [ 25 32 ], melanoma [ 33 37 ], pancreatic cancer [ 14 , 31 , 38 ] and prostate cancer [ 39 – 41 ]. Similar results have been described for the treatment of non-small-cell lung cancer (NSCLC) [ 16 ], breast cancer [ 31 , 42 ], ovarian cancer [ 31 , 43 , 44 ], hepatocellular carcinoma [ 45 , 46 ], malignant mesothelioma [ 47 , 48 ], thyroid cancer [ 49 , 50 ], oral squamous cell carcinoma [ 51 ], neuroblastoma [ 52 ] and glioma, including the difficult-to-treat glioblastoma multiform (GBM) [ 16 , 53 , 54 ].…”
Section: High-dose Vitc As a Single Agentsupporting
confidence: 69%
“…Then, cell viability was determined after 24 h at 37 °C by the MTT method. 23 As shown in Figure 8 , both coumarins have proved to be noncytotoxic against cell monolayers (CC50 = >100 μM). In parallel, the Nthy-ori 3–1 cells were incubated with 4c , 4e , and 4f (1.0 μM) for bioimaging studies and then analyzed by an epifluorescence microscope using blue (excitation 470–495 nm; emission 510–550 nm) and orange filters (excitation 530–550 nm; emission 575 nm).…”
Section: Resultsmentioning
confidence: 96%
“…Cultured cells were treated with different concentrations (10–100 μM) of 4c , 4e , and 4f . Then, cell viability was determined after 24 h at 37 °C by the MTT method . As shown in Figure , both coumarins have proved to be noncytotoxic against cell monolayers (CC50 = >100 μM).…”
Section: Resultsmentioning
confidence: 99%
“…Elevated free-radical levels can lead to the depletion of antioxidant mechanisms and the death of cancer cells. Apoptosis of breast cancer cells induced by AA at physiological concentrations (100 µM) was observed by Hong et al [ 117 ], while Tronci et al [ 118 ] demonstrated the antitumor effect of VC against papillary thyroid carcinoma cells. The oral intake of VC by patients with malignant tumors likely has no impact because, at lower concentrations, VC exhibits antioxidant, rather than pro-oxidant, activity [ 119 ].…”
Section: Vitamin Cmentioning
confidence: 99%